Performance assessment of a four-pass serpentine proton exchange membrane fuel cell with non-humidified cathode and cell state estimation without special measurement - Celik, Erman; Karagoz, Irfan (Pergamon-Elsevier Science Ltd, 2022)
Proton exchange membrane fuel cells are promising electrochemical energy conversion devices especially important for mobile technologies, including the automotive industry thanks to their quick start-up, low operation temperature, and relatively higher energy density characteristics. However, cell performance depends on many parameters like reactant temperature and humidification ratio, cell operating temperature, reactant feeding pressure, and flow field. In this study, the performance of a 50 cm(2) active area four-pass serpentine flow field hydrogen-air proton exchange membrane (PEM) fuel cell experimentally investigated for various cell operating temperatures and reactant back pressures without humidification on the cathode side. Dehydration or flooding condition of the cell is showed to be determined with tafel slope, limiting current density and types of voltage losses without using a special measurement. The results show that flooding, which is called mild flooding, is possible to be seen even at high cell temperature in a non-humidified cathode fuel cell, in case of exceeding operating pressures. Behavior of cell parameters under mild flooding and ongoing severe flooding are different from each other. Pressure increase at above 45 degrees C operating temperature is seen to served higher power output. However, at low back pressure with escalated operating temperature doesn't result with a substantial increase on performance since less amount of water is produced as a product of reaction causing membrane dehydration at relatively low current density levels thus increasing ohmic loss. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: PEM Fuel cell; Mild catalyst flooding; Flooding determination; Operating temperature; Operating pressure